Effects of mixed beech and hornbeam stands on soil properties and plant species diversity indices in Hyrcanian forests of Iran - Marefat, Simin; Eshaghi Rad, Javad; Khanalizadeh, Ameneh (Instituto de Ecología, A.C., 2020)
Revealing the effect of mixed beech and hornbeam stands on herb layer diversity is essential for sustainable forestry and biodiversity conservation since little is known in Hyrcanian forests. So, we studied the effects of such stands on understory diversity and soil physico-chemical properties in Hyrcanian forests of Iran. Forty sampled plots were established by random systematic sampling method with a regular 100 m × 200 m grid. At each sample point we recorded species identity and percent cover of each tree layer and herb layer species within plots of size 400 m2 (20 m × 20 m) and 100 m2 (10 m ×10 m) respectively. Soil samples were taken from 0 cm -10 cm and 10 cm - 30 cm soil depths. Cluster analysis was used to classify the samples based on the floristic composition data. Also detrended correspondence analysis (DCA) method was employed to assess the relationship between vegetation and environmental variables. There was no significant difference in terms of species richness, and diversity between mixed beech stands and hornbeam stands, but cluster analysis indicated that these stands were separated in two different groups based on herb layer species composition. DCA results showed that litter thickness, soil texture, total nitrogen, and organic carbon in the first layer were considered effective environmental variables in the distribution of sample plots in two stands. We observed that tree layer composition and soil characteristics were crucial contributors to variations of understory species composition which may be changed by forest management approaches over time. Tree layer composition and soil attributes can be considered effective factors for controlling and assessment of understory plant species composition. These findings could provide guidelines for conserving plant species diversity within any framework of sustainable forest management in Hyrcanian forests.